Treatment of Waldenström's macroglobulinemia with rituximab - Dimopoulos, M.A.; Zervas, C.; Zomas, A.; Kiamouris, C.; Viniou, N.A.; Grigoraki, V.; Karkantaris, C.; Mitsouli, C.; Gika, D.; Christakis, J.; Anagnostopoulos, N. (Journal of Clinical Oncology, 2002)
Purpose: Waldenström's macroglobulinemia (WM) is a low-grade lymphoplasmacytic lymphoma in which CD20 is usually expressed on tumor cells. There is evidence that patients with WM may benefit from treatment with the anti-CD20 monoclonal antibody rituximab. We performed a prospective phase II study to clearly define the activity of rituximab in patients with this disease. Patients and Methods: Twenty-seven patients with WM were treated with rituximab 375 mg/m2 intravenously (IV) for 4 weeks. Three months after completion of rituximab, patients without evidence of progressive disease received repeat 4-week courses of this agent. All patients were symptomatic, their median age was 72 years, and 15 patients were previously untreated. Results: Twelve patients (44%; 95% confidence interval, 25.5% to 64.7%) achieved a partial response after treatment with rituximab. Median time to response was 3.3 months (range, 2.2 to 7.1 months). Responses occurred in six (40%) of 15 previously untreated patients and in six (50%) of 12 pretreated patients. Patients with a serum immunoglobulin M less than 40 g/L had a significantly higher response rate. The median time to progression for all patients was 16 months, and with a median follow-up of 15.7 months, nine of 12 responding patients remain free of progression. Treatment with rituximab was well tolerated, with approximately one fourth of patients experiencing some mild form of infusion-related toxicity, usually fever and chills. Conclusion: Our prospective data indicate that rituximab is well tolerated and active in patients with WM. Previously untreated and pretreated patients seem to benefit equally. Repeat 4-week courses of rituximab may prolong the duration of response of the disease, but this observation requires confirmation in prospective, randomized trials. Furthermore, studies that will combine rituximab with chemotherapy may be relevant. © 2002 by American Society of Clinical Oncology.